2010
DOI: 10.1016/j.earscirev.2009.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Global connections between aeolian dust, climate and ocean biogeochemistry at the present day and at the last glacial maximum

Abstract: Palaeo-dust records in sediments and ice cores show that wind-borne mineral aerosol ('dust') is strongly linked with climate state. During glacial climate stages, for example, the world was much dustier, with dust fluxes two to five times greater than in interglacial stages. However, the influence of dust on climate remains a poorly quantified and actively changing element of the Earth's climate system. Dust can influence climate directly, by the scattering and absorption of solar and terrestrial radiation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
379
0
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 535 publications
(386 citation statements)
references
References 343 publications
(450 reference statements)
4
379
0
3
Order By: Relevance
“…Maher et al, 2010;Roberts et al, 2011;Larrasoaña et al, 2012;Liu et al, 2012). Roberts et al (2011) reported enhanced iron supply by aeolian dust in Eocene sediments (ODP Hole 738B) of the southern Kerguelen Plateau (Indian Ocean), where a marked increase in hematite concentrations coincided with a switch from oligotrophic to eutrophic conditions.…”
Section: Ocean Iron Fertilization and Magnetotactic Bacterial Abundanmentioning
confidence: 99%
“…Maher et al, 2010;Roberts et al, 2011;Larrasoaña et al, 2012;Liu et al, 2012). Roberts et al (2011) reported enhanced iron supply by aeolian dust in Eocene sediments (ODP Hole 738B) of the southern Kerguelen Plateau (Indian Ocean), where a marked increase in hematite concentrations coincided with a switch from oligotrophic to eutrophic conditions.…”
Section: Ocean Iron Fertilization and Magnetotactic Bacterial Abundanmentioning
confidence: 99%
“…Globally distributed climate records show that the global emission of dust was significantly higher during the most recent glacials than during interglacials such as the present (e.g., Maher et al, 2010;Mahowald et al, 2011;McGee et al, 2010). For example the analysis of dust particles in ice cores from the Antarctic continent shows that throughout the last 800 ka the dust flux to Antarctica was 25 times higher during glacials than during interglacials (Lambert et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This heterogeneous mixture of aerosols, i.e. dust, plays an important role in global climate (Maher et al, 2010) as it influences the radiative forcing of the atmosphere (Mahowald et al, 2006b), and can be a source of nutrients (e.g., iron) to the open ocean that can lead to a strengthening of the biological pump (Fung et al, 2000;Martin, 1990;Mills et al, 2004). In addition, dust particles influence cloud formation by providing cloud condensation nuclei (Mahowald and Kiehl, 2003), and can affect the albedo of ice sheets (Ridgwell, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The role of dust in sedimentary systems is apparent in oceanic settings remote from continents where significant dust mantles the ocean floor (Hesse, 1994;McGee et al, 2007;Rea, 1994). Copious dust transport and deposition marked the glacial cycles of the Quaternary Period, resulting in accumulation of loess downwind of cold climate regions, most notably in China where loess deposits of up to 100 m date from this time, but also in Eurasia, North America, Northern Europe, southern South America and New Zealand (Maher et al, 2010). Dust therefore played a major role in biogeochemical processes during cold climate phases.…”
Section: Introductionmentioning
confidence: 99%